Transcriptomic and metabolomic approaches to investigate the molecular responses of human cell lines exposed to the flame retardant hexabromocyclododecane (HBCD). Issue 8 (December 2015) - Zhang, Jinkang; Williams, Timothy D.; Abdallah, Mohamed Abou-Elwafa; Harrad, Stuart; Chipman, James K.; Viant, Mark R.
Abstract The potential for human exposure to the brominated flame retardant, hexabromocyclododecane (HBCD) has given rise to health concerns, yet there is relatively limited knowledge about its possible toxic effects and the underlying molecular mechanisms that may mediate any impacts on health. In this study, unbiased transcriptomic and metabolomic approaches were employed to investigate the potential molecular changes that could lead to the toxicity of HBCD under concentrations relevant to human exposure conditions using in vitro models. A concentration-dependent cytotoxic effect of HBCD to A549 and HepG2/C3A cells was observed based on MTT assays or CCK-8 assays with EC50 values of 27.4 μM and 63.0 μM, respectively. Microarray-based transcriptomics and mass spectrometry-based metabolomics revealed few molecular changes in A549 cells or HepG2/C3A cells following a 24-hour exposure to several sub-lethal concentrations (2 to 4000 nM) of HBCD. Quantification of the level of HBCD in the HepG2/C3A exposed cells suggested that the flame retardant was present at concentrations several orders of magnitude higher than those reported to occur in human tissues. We conclude that at the concentrations known to be achievable following exposure in humans, HBCD exhibits no detectable acute toxicity in A549 cells, representative of the lung, or in HepG2/C3A cells, that are hepatocytes with some xenobiotic metabolic capacity.